OP36 Prevalence of advance care directives among older australians accessing health and residential aged care services: multi-centre audit study. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Nolte, L; Buck, K; Ruseckaite, R; Kelly, H; Sellars, M; Sinclair, C; Clayton, J; Detering, K
Abstract : Background: Advance care planning (ACP) is a priority in Australian health policy, legislation and accreditation standards. ACP supports people to consider and communicate their future treatment preferences and document them in an advance care directive (ACD). However, the availability of ACDs at the point of care amongst Australians is unknown. The aim of this study was to describe the prevalence of ACDs in those aged ≥65 years accessing general practice (GP), hospitals and residential aged care facilities (RACF). Methods: A prospective multi-centre health record audit. Literature review informed the methodology. Auditors received education and jurisdictional-specific audit manuals. Recruitment of organisations was via expression of interest. The primary outcome was presence of an ACD. Results: Fifty-one sites participated (13 GPs, 12 hospitals, 26 RACFs), representing six jurisdictions. 2, 285 health records were audited; 503 attending GPs, 574 in hospitals, and 1, 208 in RACFs. 30% of people had at least one ACD. Most (21%) were non-statutory documents. The prevalence of statutory ACD-preferences for care was 3%; the prevalence of statutory ACD-substitute decision-maker was 11%. ACD prevalence in GP was low (3%) compared to hospitals (16%) and RACFs (48%). Conclusions: Approximately 30% of older Australians had at least one ACD in their health record, and the majority of these were non-statutory ACDs. Priorities to increase accessibility of documentation may include improved policy, promotion of ACD uptake amongst older persons, storage within health record systems, workforce education and training, information resources, and ongoing prevalence monitoring. These initiatives are required across all sectors, especially GP.